Community Participation and Educational Decentralization in Gbawe Cluster of School, Ga South Municipality - Dzikunu, Cosmos Kwame; Asiaman, Michael; Pajibo, Edison (Global Journal of Social Sciences Studies, 2019)
This research sought to assess the influence of community participation on educational decentralization in Gbawe, Ga South Municipality in terms of stakeholders’ contribution to educational decentralization. A concurrent mixed method design was adopted. Semi-structured interviews and questionnaires were the data collection instruments. A sample size of 108 comprising Municipal Chief Executive, Municipal Director of Education, SMCs and PTA Chairpersons, teachers and parents constituted the study. These were sampled through purposive and random cluster sampling techniques. Descriptive statistics were utilized for the quantitative data analysis while the thematic approach was used for the qualitative data. The findings of the study revealed that parents’ level of formal education, their attitude towards PTA meetings, their perceptions about the literate population among them and the attitude of SMCs and PTAs towards school finance affected local level participation and educational administration. The study affirmed that decentralization is an effective tool for development in the Gbawe cluster of schools. Based on the findings and conclusions drawn, it is recommended that stakeholders or authorities in the realm of education should endeavour to give community members the opportunity to contribute to educational decentralization. Also, a portion of the Municipal Assembly Common Fund meant for education should be increased to meet the current educational needs of local communities.